PENGGUNAAN BAHAN AJAR STRUKTUR ALJABAR UNTUK MENINGKATKAN KEMAMPUAN PEMBUKTIAN MATEMATIS PADA MAHASISWA IKIP PGRI PONTIANAK - Jamilah, Jamilah; Fadillah, Syarifah (Universitas Tanjungpura, 2017)
This study aims to know the effect of teaching and learning using Algebraic Stucture materials based on mathematical proof to improve mathematical proof ability. The type of this study is experimental method with One Shot Case Study design. Population in this study is students of 6th semester in Departement of Mathematics Education and sample is students in class A and B which are consist of 83 students. The results show that teaching and learning using Algebraic Structure materials based on mathematical proof can improve mathematical proof ability with 16Z0bs=9,74>1,645=Z0,05